Comparison of biological and biochemical neutralization tests to detect neutralizing antibodies against SARS-CoV-2 - Maljanen, Sari (My University, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causing agent of the coronavirus disease (COVID-19), has been the subject of worldwide attention since the emergence of this new virus in 2019. An instant need to develop therapeutic drugs, vaccines, and diagnostic methods for SARS-CoV-2 has encouraged the scientific community around the world to collaborate and publish information promptly to assist in the fight against COVID-19. Urgent testing of high-risk groups, evaluation of antibody-mediated protection from recovered COVID-19 patients and vaccinees have resulted in many newly developed immunoassays. Analyses of neutralizing antibodies against SARS-CoV-2 are based on the interaction between the host angiotensin-converting enzyme 2 (ACE2) receptor protein and the receptor-binding domain (RBD) of the coronavirus. However, several tests still await clinical validation and formal approval. Therefore, a robust and accurate serological assay to measure neutralizing antibodies against SARS-CoV-2 is still needed. The current gold standard for assessment of the antibody status is the virus microneutralization test (MNT) using live virus, which in the case of SARS-CoV-2 requires biosafety level 3 (BSL-3) laboratory and is tedious and time-consuming. In this study, we developed a biochemical surrogate virus neutralization test (sVNT) intended to replace the demanding MNT. We compared results from different sVNT plate formats to MNT results of COVID-19 patients at convalescent phase and Pfizer-BioNTech COVID-19 vaccinated (COMIRNATY®) individuals. The developed new sVNT assay does not require BSL-3 laboratory, target cells, viruses, or highly skilled operators, and could be used in diagnostics of SARS-CoV-2 infections and possibly extended for the diagnosis of other highly pathogenic virus infections.
Keywords: Surrogate virus neutralization test, neutralizing antibody, SARS-CoV-2, coronavirus